OS06.4A Identification of T cell receptors targeting ZFTA-RELA fusion-positive ependymoma. (9th September 2021) - Kehl, N; Friedrich, M; Kilian, M; Zheng, T; Pajtler, K; Bunse, L; Platten, M
Abstract: BACKGROUND: The oncogenic gene fusion between ZFTA (formerly C11orf95) and RELA has in recent years been highlighted as oncogenic driver event ultimately leading to malignant transformation and progression of ependymoma. Representing a genetic hallmark in 17.6% of ependymomas, ZFTA-RELA fusion-positive tumors qualified as separate diagnostic entity in the 2016 revision of the WHO classification of CNS tumors. This tumor entity mainly occurs in pediatric patients and is characterized by poor prognosis and the lack of biology-driven therapy. RESULTS: De novo prediction of putative gene fusion-derived neoepitopes in malignant CNS diseases yielded several potential candidates suitable for screening. Of these, vaccination of A2.DR1-transgenic major histocompatibility complex (MHC)-humanized mice with in silico compiled peptide vaccines encompassing the ZFTA-RELA fusion sequence elicited robust antigen-specific CD4 + -restricted immune responses. We identified ZFTA-RELA -reactive T cell clones by multiplexed Interferon-γ / Interleukin-2 recall response. Single-cell VDJ-sequencing of reactive T cells demonstrated a highly clonal T cell receptor (TCR) repertoire and shared clonotypes among all vaccinated animals. Matching TCRα/β chains have been assembled from single-cell sequencing data and cloned for functional testing of neoepitope-reactive TCR-transgenic T cells in vitro as well as in vivo using a transposon system-based immunocompetent, MHC-humanized ZFTA-RELA fusion-positive ependymoma model. CONCLUSION: Here we identify the oncogenic ZFTA-RELA gene fusion product as a novel tumor-specific neoepitope that is recognized by MHC class II-restricted TCRs. Therapeutic efficacy of TCR-transgenic cell therapy can be further investigated using an immunocompetent MHC-humanized mouse model of ZFTA-RELA fusion-positive ependymoma. Our findings provide initial evidence for neoepitope-specific immunotherapy in pediatric CNS tumors.